Meta-Analysis of Risk Factors for Bile Leakage After Hepatectomy Without Biliary Reconstruction - Tan, Ling; Liu, Fei; Liu, Zi-lin; Xiao, Jiang-wei (Frontiers in Surgery, 2021)
Background and Aim The risk factors for bile leakage after hepatectomy without biliary reconstruction are controversial. This study investigated the risk factors for bile leakage after hepatectomy without biliary reconstruction. Methods We searched databases (Embase (Ovid), Medline (Ovid), PubMed, Cochrane Library, and Web of Science) for articles published between January 1, 2000, and May 1, 2021, to evaluate the risk factors for bile leakage after hepatectomy without biliary reconstruction. Results A total of 17 articles were included in this study, and the overall results showed that sex, diabetes, left trisectionectomy, central hepatectomy, extended hepatectomy, segment I hepatectomy, postoperative drainage tube, intraoperative blood transfusion, anatomical hepatectomy and intraoperative bleeding ≥1000 ml were risk factors for biliary leakage. Age >75 years, cirrhosis, underlying liver disease, left hepatectomy, right hepatectomy, benign disease, Child–Pugh class A/B, and preoperative albumin <3.5 g/dL were not risk factors for bile leakage after hepatectomy without biliary reconstruction. Conclusion Comprehensive research in the literature revealed that sex, diabetes, left trisectionectomy, central hepatectomy, extended hepatectomy, segment I hepatectomy, postoperative drainage tube, intraoperative blood transfusion, anatomical hepatectomy and intraoperative bleeding ≥1000 ml were risk factors for biliary leakage.